Illness characteristics and symptoms in an Irish early intervention for psychosis service. (18th December 2014) - Lyne, J. P.; O'Donoghue, B.; Roche, E.; Behan, C.; Jordan, I.; Renwick, L.; Turner, N.; O'Callaghan, E.; Clarke, M.
Abstract : Objectives: Study of illness characteristics and symptoms in a young population with psychosis can assist for understanding of their needs, and can inform service planning strategies. The aims of the current study were to describe illness characteristics and symptoms of a first episode psychosis (FEP) sample aged 25 years and under, and compare with a sample aged over 25 years. Methods: Interviews were conducted for 437 individuals aged 16–65 years presenting with suspected psychosis between 2005 and 2012 in a defined catchment area (population of 390 000) using the Structured Clinical Interview for DSM IV to determine the presence of a psychosis diagnosis. Individuals with confirmed psychosis were assessed using standardised instruments to determine illness characteristics at first presentation. Results: Among the 25 years, and under FEP sample, 23.9% had their first onset of symptoms (prodromal or psychotic) before 18 years of age. After controlling for confounders, the sample aged 25 years and under had a significantly shorter log transformed duration of untreated psychosis ( p =0.002), more negative symptoms ( p =0.045) and greater frequency of comorbid cannabis abuse diagnosis ( p =0.027). Conclusions: Symptom onset in a youth FEP sample frequently occurs before age 18 years. Certain illness characteristics differed across the age categories, such as greater negative symptoms and cannabis abuse in the youth sample. Overall, the findings support the provision of adequate strategies for management of negative symptom deficits and substance abuse across all ages in FEP.